Soy isoflavones alleviate polycystic ovary syndrome in rats by regulating NF- κB signaling pathway. Issue 1 (1st January 2021) - Ma, Xiaohong; Li, Xiaorong; Ma, LiLi; Chen, Yan; He, Shengyu
ABSTRACT: Soy isoflavones have been widely used in the treatment of clinical gynecological diseases. The aim of this study was to investigate the therapeutic effect and molecular mechanism of Soy isoflavones on rats with polycystic ovary syndrome (PCOS). Sprague-Dawley rats were orally administered 1 mg/kg letrozole for 21 consecutive days to induce the PCOS rat model. After PCOS induction, Soy isoflavones (100 mg/kg) or metformin (Positive control; 500 mg/kg) was administered continuously for 28 days. Then, H&E staining was used to observe the pathological changes of ovary. The serum hormone levels and the levels of antioxidant and inflammatory cytokines in ovarian tissue were detected. Additionally, the expression of NF-κB signaling pathway protein was detected by Western blot. Our results showed that soy isoflavones treatment significantly reduced the body weight, ovarian volume and weight, and improved estrous cycle in PCOS rats. H&E staining showed that the number of cystic dilated follicles and atretic follicles in ovarian tissue diminished, showing healthy follicles and corpus luteum. In addition, soy isoflavones treatment markedly decreased serum testosterone and luteinizing hormone (LH) levels, as well as oxidative stress levels and inflammation levels, and increased estradiol (E2) and follicle stimulating hormone (FSH) levels. At the same time, Soy isoflavones treatment inhibit the phosphorylation level of NF-κB p65 and increased the IκBα expression in ovarian tissues of PCOS rats. Overall, Soy isoflavones can improve ovarian morphology and hormone disorders in PCOS rats by inhibiting the activity of NF-κB pathway and enhancing anti-inflammatory and antioxidant capacity.